2020
DOI: 10.2174/1568026620666200502005411
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Flavonoids as Potential Anticancer Drug Including Synergy with Other Approaches

Abstract: Background: In cancer chemotherapy, conventional drugs aim to target the rapidly growing and dividing cells at the early stages. However, at an advanced stage, cancer cells become less susceptible because of the multidrug resistance and the recruitment of alternative salvage pathways for their survival. Besides, owing to target non-selectivity, healthy proliferating cells also become vulnerable to the damage. The combination therapies offered using flavonoids to cure cancer not only exert an additive effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 180 publications
0
12
0
Order By: Relevance
“…Therefore, this finding indicates that other action mechanisms may contribute to the efficacy of the HDS-1 extract beyond bioenhancers for paclitaxel. According to previous findings, two possibilities are posed as follow: Taxus-derived taxane compounds may contribute to the in vivo anti-cancer effect due to the cytotoxicity property [ 57 ], or flavonoids or lignoids may exert a synergistic effect to enhance PTX's efficacy [ 58 , 59 ]]. The latter hypothesis is confirmed by the MTT assay in our investigation, and we find that HDS-2 (flavonoids) and HDS-3 (lignoids) exert a synergistic effect with paclitaxel toward A549 growth in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this finding indicates that other action mechanisms may contribute to the efficacy of the HDS-1 extract beyond bioenhancers for paclitaxel. According to previous findings, two possibilities are posed as follow: Taxus-derived taxane compounds may contribute to the in vivo anti-cancer effect due to the cytotoxicity property [ 57 ], or flavonoids or lignoids may exert a synergistic effect to enhance PTX's efficacy [ 58 , 59 ]]. The latter hypothesis is confirmed by the MTT assay in our investigation, and we find that HDS-2 (flavonoids) and HDS-3 (lignoids) exert a synergistic effect with paclitaxel toward A549 growth in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, often known as cell death, is the result of an irreversible halt in the cell cycle. By interrupting the cell cycle during the S phase, RES could delay cell cycle progression and limit the development of rat C6 glioma cells [ 125 ]. Oncogenic microRNAs (miRs) such as miR-19, miR-21, and miR-30a-5p were shown to be repressed in glioma cells, which was connected to alterations in the expression of their target genes such as p53, NF-KB, EGFR, STAT3, COX-2, and the PI3K/AKT/mTOR signaling pathway.…”
Section: Control Of Cellular Proliferation Apoptosis and Differentiationmentioning
confidence: 99%
“…However, further progress in precision medicine in the twenty-first century enables an individualized approach in the context of predictive, preventive, and personalized medicine that can improve cancer management [18,[61][62][63][64][65][66]. Cancer treatment can also be improved by applying natural substances, which sensitize cancer cells to therapeutic agents [67][68][69][70].…”
Section: Anti-cancer Therapy: From Conventional To Advanced Approachesmentioning
confidence: 99%
“…Other clinical trials revealed the potential of flavonoids as anticarcinogenic agents [80] and as complementary antitumor agents in colorectal cancer patients [45]. However, the significant capacity of flavonoids to improve therapeutic outcomes by improving the treatment sensitivity or reversing the resistance of cancer cells to anti-cancer therapeutic agents is currently evaluated predominantly in preclinical in vitro and in vivo research [67][68][69][70].…”
Section: Flavonoids: Origin and Classificationmentioning
confidence: 99%